Strategic Planning and Performance: A Quantitative Study - Nazari, Mehrdad; Desai, Kavitha (International Journal of Innovation Management and Organizational Behavior (IJIMOB), 2023)
Objective: Employee engagement is a pivotal factor in organizational success, influencing productivity and retention. This study aims to evaluate how role flexibility and employee planning affect employee engagement at Tata Motors, exploring these relationships within the context of an evolving automotive industry.Methodology: A cross-sectional survey was conducted among 350 employees of Tata Motors, using the Utrecht Work Engagement Scale, Role Flexibility Scale, and Employees' Planning Scale. Data were analyzed through Pearson correlation to assess relationships between variables and linear regression to determine their predictive power on employee engagement.Findings: Descriptive statistics revealed moderate to high levels of engagement (M=4.56, SD=0.98), role flexibility (M=3.89, SD=0.75), and planning (M=4.20, SD=0.88). Pearson correlation coefficients indicated significant positive relationships between employee engagement and role flexibility (r=0.62, p